Bond disproportionation and dynamical charge fluctuations in the perovskite rare-earth nickelates - Green, Robert J.; Haverkort, Maurits W.; Sawatzky, G. A. (Physical review, 2016)
We present a theory describing the local electronic properties of the perovskite rare-earth nickelates—materials which have negative charge transfer energies, strong O 2p - Ni 3d covalence, and breathing-mode lattice distortions at the origin of highly studied metal-insulator and antiferromagnetic ordering transitions. Utilizing a full-orbital, full-correlation double-cluster approach, we find strong charge fluctuations, in agreement with a bond disproportionation interpretation. The double-cluster formulation permits the inclusion of necessary orbital degeneracies and Coulomb interactions to calculate resonant x-ray spectral responses, with which we find excellent agreement with well-established experimental results. This previously absent, crucial link between theory and experiment provides validation of the recently proposed bond disproportionation theory, and provides an analysis methodology for spectroscopic studies of engineered phases of nickelates and other high-valence transition-metal compounds.